Factors associated with attention-deficit/hyperactivity disorder among Tunisian children - Guedria, Asma; Guedria, Mohamed; Ben Fredj, Manel; Ayoub, Randaline; Ben Abid, Hela; Mhalla, Ahmed; Slama, Hela (Frontiers in Psychiatry, 2025)
IntroductionAttention-deficit/hyperactivity disorder (ADHD) is a chronic neurodevelopmental condition that affects millions of children and adolescents worldwide. Knowledge of risk factors associated with ADHD may reduce its prevalence and its severe impact on patient’s quality of life. The aim of this study was to identify risk factors associated with ADHD and to discuss their involvement in the genesis of the disorder.MethodsThis is a case-control study involving a first group of 74 children (mean age = 9 years) diagnosed with ADHD. The second group included 80 healthy control children. They were randomly selected and matched for age and gender. A literature-based questionnaire assessing the socio-demographic data, biological and environmental factors associated with ADHD was administered to the parents. The diagnosis of ADHD group was made by a trained child psychiatrist according to the DSM-5 criteria supplemented by the Conners scales of parents and teachers. For the control group, we added to the questionnaire the MINI-kid section of ADHD to screen for possible presence of ADHD symptoms. Univariate then multivariate analyses were conducted to identify factors associated with ADHD.ResultsSeveral factors were more prevalent in children with ADHD than in controls: disturbed family dynamics, low socio-economic status, family history of psychiatric and organic pathologies, and particularly several early environmental factors, including passive smoking during pregnancy, prematurity, fetal distress, caesarean delivery and low birth weight. In the early childhood period, early exposure to television was also strongly associated with ADHD. However, the multivariate model conducted to determine the variables independently associated with ADD/ADHD revealed only three determining factors: passive smoking during pregnancy (OR = 4.60 [2.14, 9.94]; p < 0.001), acute fetal distress (OR = 5.08 [1.47, 17.52]; p = 0.01), and familial psychiatric history (OR = 9.37 [2.46, 35.59]; p = 0.001).DiscussionThe recognition of factors involved in the genesis of ADHD within different ethnic populations may help understanding and broaden our knowledge of this disorder to develop targeted strategies for prevention and early intervention. Further participants with more robust statistical output are required to confirm our findings to a more generalized population.